Effect of Nitrogen Sources on Photosynthesis and Biosynthesis of Alkaloids and Leaf Volatile Compounds in Annona sylvatica A. St.-Hil - Corrêa, Patricia Luciana Carriel [UNESP]; De-la-Cruz-Chacón, Iván; Sousa, Marília Caixeta [UNESP]; Vieira, Maria Aparecida Ribeiro [UNESP]; Campos, Felipe Girotto [UNESP]; Marques, Marcia Ortiz Mayo; Boaro, Carmen Sílvia Fernandes [UNESP]; Ferreira, Gisela [UNESP] (Springer Nature, 2022)
Nitrogen (N) has been reported to act on both primary and specialized metabolism of plants. However, it is not clear how different N sources affect metabolism in species of the genus Annona. Thus, the aim of the work was to analyze how nitrate (NO3−) and ammonium (NH4+) influence photosynthesis and the production of alkaloids and leaf volatile compounds in Annona sylvatica A. St.-Hil. Plants were submitted to four treatments [NH4+, NO3−, NO3−:NH4+, and no N (W/N)], in hydroponic cultivation, and collected at 30, 60, and 90 days after the beginning of treatments. Plants maintained in NH4+ showed greater photosynthetic activity, high production of total alkaloids, in particular liriodenine, and increased production of leaf volatile compounds commonly related to stress situations. On the other hand, plants cultivated with NO3− showed lower photosynthetic activity and higher production of leaf volatile compounds related to plant resistance and defense. A. sylvatica seedlings are adapted to NH4+ with energy resources used to increase both primary and specialized metabolism, while using NO3−, the lower energy availability leads A. sylvatica plants to invest in leaf defense and not in photosynthesis. The individual use of NH4+ and NO3− increases the phytochemical potential of the species by stimulating the production of different groups of specialized metabolites.
Keywords: Ammonium; Annonaceae; Liriodenine; Nitrate; Primary metabolism; Specialized metabolism